(untitled) (Indian Journal of Child Health, 2019)
Background: Exposure to diabetes in utero has been established as a significant factor for certain component of the clinical syndrome. Although complications of atherosclerosis occur in adult life, the process begins in early childhood. Hence, measuring aortic intima-media thickness (AIMT) in the newborn is a feasible, accurate, and sensitive marker of atherosclerotic risk. Objective: The objective of the study was to find an association of AIMT with cord blood lipid levels and anthropometric factors. Methods: Babies born to diabetic mothers (gestational diabetes mellitus/type 2 diabetes mellitus (34 weeks–42 weeks) who were taken as one group and babies born to non-diabetic mothers (34 weeks–42 weeks) who were taken as the other group were enrolled in this study. Lipid values were measured of umbilical cord blood, collected immediately after delivery. Atherogenic-indices were calculated; neonatal anthropometric measurements were taken within 24 h after delivery. Abdominal AIMT (aAIMT) was measured within 4 days of delivery using a high-resolution ultrasound B mode by a trained radiologist. Maternal age, parity, height, pre-pregnancy weight, gestational age, and other investigations were taken from maternal records. Results: In this study, birth weight (BW) was positively correlated with triglycerides (TG), cholesterol, high-density lipoprotein (HDL), very low-density lipoprotein (VLDL), and atherogenic-indices, whereas, it was negatively correlated with low-density lipoprotein (LDL) (p<0.01). A positive correlation was found between aAIMT and BW, abdominal circumference, TG, cholesterol, HDL, LDL, VLDL, and atherogenic-indices (p<0.001). Conclusions: In this study, infants born to diabetic mothers had higher anthropometry, lipid values, aAIMT compared to babies born to non-diabetic mothers without risk factors.